The Effectiveness of Flipped Classroom in Improving Students' Learning Outcomes - I Gusti Ayu Dewi Paramita; Evin Yudhi Setyono; Ni Nyoman Yuliantini; Ni Ketut Suciani (Soshum: Jurnal Sosial dan Humaniora, 2023)
An appropriate learning method is a basic way for learners to be able to achieve maximum grades and the achievement of existing learning objectives. The Flipped Classroom method is one of the new methods in Indonesia which can be one of the preferred methods that can be applied in teaching English. Surely, a trial is required to measure its effectiveness. The current study has two purposes, the first one was to determine whether the Flipped Classroom learning method was able to effectively improve student learning outcomes, especially in English lectures. Then, secondly, the purpose was how to apply Flipped Classroom in the classroom. This research is quantitative descriptive research with a quasi-experimental approach, employing a "Pretest – Posttest Non-Equivalent Control Group Design". The current study involved 2 groups, namely the experimental group, taught using Flipped Classroom learning and the control group taught using conventional learning (without flipped Classroom design). It was found that the value of sig. Levene's test is 0.696 > 0.05, indicating that the data variance between the control class and the experimental class is homogeneous. Furthermore, the value of sig. (2-tailed) for the t-test, the value produces a value of 0.000 <0.05, then the decision-making in the t-test is to reject the Ho hypothesis and accept the Ha hypothesis. Thus, it can be interpreted that there is a significant difference between the average N-Gain scores of the control and experimental classes in English Engineering. It can be concluded that Flipped Classroom is effective in improving students' English skills in the topic of Describing Processes, as evidenced by the N-Gain value of 90, 91% which is included in the effective category. In other words, Flipped Classroom is effective to increase the students' scores in the class.